Cybeye- AI/ML Driven Compromise Detection Tool for Cyber Threat Intelligence - Meruva Ashish; Arun Kumar B. R; Abhishek K Sridhar; Nagashree L; Sreeahk G (Journal of Information Security System and Cyber Criminology Research, 2024)
In an increasingly interconnected world, cyber security has become a paramount concern. The rapid proliferation of digital systems has exposed organizations to a growing threat landscape, with malicious actors constantly seeking to breach network defences. Developing robust Compromise Detection Systems (CDS) has become essential to combat this evolving threat landscape. This project aims to design and implement an AI/ML-driven Compromise Detection System that leverages machine learning algorithms to enhance network security by efficiently identifying and mitigating potential threats. The objectives of this project are to enhance detection accuracy and cost-effectiveness in the realm of network security. By incorporating advanced machine learning models, our CDS can discern subtle patterns within vast datasets, significantly improving the accuracy of compromise detection. It is an AI/ML tool that can detect whether a system is compromised. The fusion of AI/ML with compromise detection promises to revolutionize the field, providing organizations with a powerful tool to defend against the evolving and sophisticated landscape of cyber threats. System Vulnerability Assessment plays a pivotal role in cybersecurity, serving as a cornerstone for identifying and mitigating potential weaknesses that malicious actors could exploit. It encompasses a systematic process to identify and quantify vulnerabilities in any network component, thereby facilitating the proactive management of cybersecurity risks. The primary objective of vulnerability assessment is to diminish the likelihood of security breaches by pre-emptively identifying and rectifying flaws within systems and networks. Robust vulnerability assessment practices must be addressed in the contemporary landscape of cyber threats and evolving technological ecosystems. By conducting comprehensive vulnerability assessments, organizations can enhance their resilience against cyber-attacks, fortify their defences, and safeguard critical assets. This paper explores the significance of system vulnerability assessment, delineating its methodologies, challenges, and implications for cybersecurity resilience in an increasingly interconnected world.